FROM NEGATIVE TO POSITIVE PEACE: STRENGTHENING THE ROLE OF YOUTH IN RELIGIOUS PEACEBUILDING IN BUKITTINGGI, WEST SUMATRA - Zulfan Taufik (Akademika : Jurnal Pemikiran Islam, 2020)
Youth as religious peacebuilding actors still receive less attention in academic studies and peace praxis. It often makes youth being depicted as victims or as perpetrators of violence in religious conflict. This study specifically seeks to explore the efforts of youth involvement and also to strengthen the capacity of the youth in making religious peacebuilding in Bukittinggi, West Sumatra. By using the action research method, this research found that Bukittinggi is at negative peace, which is still at the level of mere absence of war and saving the seeds of mutual suspicion between interfaith believers. It is undoubtedly because of a lack of interaction and openness between the interfaith believers. As for the strengthening efforts are undertaken through interfaith youth forum, youth for peace workshop, and the initiation of the interfaith youth organization. That various efforts give hope for the future of religious peace in Bukittinggi from negative peace to positive peace. It is because youth offer creative energy and active potential to transform violent conflict and foster active peace. Keywords: Youth, Religious Peacebuilding, Negative Peace, Positive Peace, Bukittinggi.